An Assessment of How Facial Mimicry Can Change Facial Morphology: Implications for Identification1. Issue 2 (1st December 2016) - Gibelli, Daniele; De Angelis, Danilo; Poppa, Pasquale; Sforza, Chiarella; Cattaneo, Cristina
Abstract: The assessment of facial mimicry is important in forensic anthropology; in addition, the application of modern 3D image acquisition systems may help for the analysis of facial surfaces. This study aimed at exposing a novel method for comparing 3D profiles in different facial expressions. Ten male adults, aged between 30 and 40 years, underwent acquisitions by stereophotogrammetry (VECTRA‐3D ® ) with different expressions (neutral, happy, sad, angry, surprised). The acquisition of each individual was then superimposed on the neutral one according to nine landmarks, and the root mean square (RMS) value between the two expressions was calculated. The highest difference in comparison with the neutral standard was shown by the happy expression (RMS 4.11 mm), followed by the surprised (RMS 2.74 mm), sad (RMS 1.3 mm), and angry ones (RMS 1.21 mm). This pilot study shows that the 3D–3D superimposition may provide reliable results concerning facial alteration due to mimicry.